Escola, consumo e projetos de vida na visão de jovens estudantes de uma escola pública e outra privada no interior do estado de São Paulo - Cinati, Anderson (Universidade Federal de São Carlos, 2016)
The guidelines that establish the Basic Education in Brazil are the same to public and private schools, however, the education developed with students from both groups can have different directions. The relation between the different socioeconomic contexts, normally existent, can cause different perceptions regarding the opportunities that these students will have during the construction of their life projects and their future perspectives. In this context, this research sought to discuss the relationship between the consumption and the life project under the view of young students from a public school and a private one, trying to understand how these elements make us rethink the education in a critical way. To reach the proposed goal, it was chosen two schools in São Paulo’s countryside, where the researcher works as Geography and History teacher. High school students, mainly seniors, participated in this research. The methodology used was initially based on a quiz given in these schools and, later on, semistructured interviews were developed. This way, general data was collected in order to find out the socioeconomic profile of the groups, apart from trying to identify the relation with the consumption, the school and the life projects of these students. It was possible to conclude that the life projects of these students tend to be individualists and oriented many times by the power of consumption as, between the interviewed, there was no student that showed concerns on social or environmental context. It was presented as proposals to improve these issues, the increase of educational public policies, besides the projects that can be developed in the schools, in order to favor the development of a emancipatory education about current society. In this context, themes and directions about how to make these discussions were suggested, in order to evolve the role of the different classes in the maintenance of social structures, rethinking the origin of inequality, racial, historical, school and family issues. If the life project is uncritical, these individuals may not be clear of what really happens in the society, in respect of having or not. Their projects can summarize in acquisition of a determined social status to make their consumption dream.
Keywords: Projeto de vida; Consumo; Ensino médio; Escola pública; Escola privada; Life project; Consumption; High School; Public school; Private school; CIENCIAS HUMANAS::EDUCACAO